THE PALEOENVIRONMENTAL CONDITIONS OF THE PERVOMAISKY BIOGENIC BUILDUP COMMUNITY (HAUTERIVIAN OF THE RIVER BODRAK - Popova, L. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The Pervomaisky biogenic buildup (Hauterivian of Bodrak-Alma interfluve) was developing from the shoal reef to atoll according to classic scheme, and then was overlapped with offshore deposits. The changes in the trophic structure of the community, in the morphological diversity of populations and in the mortality curves were studied. These analyses suggest that the community occurred under oxygen deficiency conditions. The main factor of stress was the rise of temperature; terrigenous material supplying was subordinate one. The oxygen deficiency arose from the degradation of the scleractinian community. The structure of the reef heterotrophic component was affected by stress first; autotrophic (scleractinian-zooxanthellan) component stunting was more gradual.